Potential use of mealworm frass as a fertilizer: Impact on crop growth and soil properties - Houben, David; Daoulas, Guillaume; Faucon, Michel-Pierre; Dulaurent, Anne-Maïmiti (Scientific reports, 2020)
Rearing insects is expected to dramatically increase during the next few years, and this will be associated with generating high quantities of frass (insect excreta). It is necessary to find solutions allowing the efficient valorization of these by-products before a major upscaling of the industry takes place. Therefore, this study aims at investigating the fertilizer potential of frass. A pot experiment was established and soil was amended either with mealworm ( Tenebrio molitor L.) frass (10 Mg ha −1 ), with mineral fertilizer (NPK) at equivalent nutrient level to frass or with a mixture of 50% NPK and 50% frass. Changes of soil properties and growth and nutrient uptake by barley ( Hordeum vulgare L.) were then analyzed. Due to its rapid mineralization and the presence of nutrient in a readily-available form, we found that frass is as efficient as mineral NPK fertilizer to improve biomass and N, P and K uptake by barley. Compared to mineral fertilizer, water soluble P concentration is five times lower in the presence of frass, which prevents P from loss and sorption onto soil constituents. More importantly, BIOLOG EcoPlate reveals that addition of frass stimulates soil microbial activity, especially when it is mixed with mineral fertilizer, suggesting a synergistic effect between both amendments. Taken together, our results indicate that frass has a great potential to be used as a partial or a complete substitute for mineral NPK fertilizer. This is especially relevant in the context of a reduced availability of mineral fertilizers while being consistent with circular economy’s principles.